Innovative technology of hip-potherapy in complex treatment of manifestations of dysplastic and dystrophic syndrome in children - V. N. Kuvina (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The article presents pathomechanical grounding of application of designed method of hippotherapy in treatment of manifestations of dysplastic and dystrophic syndrome with evaluation of remote outcomes of complex treatment in 5 years in 120 children. The basics of therapeutic impact of horse riding lie in natural movements of a horse, helping a rider to organize and systematize his or her movements. Hippotherapy (with performing special correcting exercises) as a method of complex treatment of children with dysplastic and dystrophic syndrome forms the skill of space orienting, improves coordination of movements, strengthens and trains muscles. Together with all that it improves psychoemo-tional state of a patient. This method of treatment of combined pelvis and spine deformity in children in comparison with other known techniques provides expressed therapeutic effect due to simultaneous correction of pelvic and spinal muscles, development of muscular-articular perception and muscular-sensor coordination, and also due to reconstruction and formation of a new movement stereotype.